A CRITICAL PATH METHOD APPROACH TO A GREEN PLATFORM SUPPLY VESSEL HULL CONSTRUCTION - TURAN, EDA; GUNER, Mesut (International Journal of Industrial Engineering: Theory, Applications and Practice, 2013)
This study generates a critical path method approach for the first Green Platform Supply Vessel hull constructed in Turkey. The vessel was constructed and partly outfitted in a Turkish Shipyard and delivered to Norway. The project management of the vessel was conducted utilizing Critical Path Method (CPM) and the critical paths during construction and partly outfitting period of this sophisticated vessel were presented. Additionally, the precautions in order to prevent the delay of the project were discussed.